Case Report of Isolated Hepatic Tuberculosis (Bangladesh Journal of Medicine, 2015)
Tuberculosis is one of the most common diseases in Bangladesh and has variable clinical manifestations. Isolated Hepatic tuberculosis is not a common disease; in fact the presentation of hepatic tuberculosis may be without having history of any active Pulmonary TB or military TB. Patient usually present without having any typical symptoms; so it is difficult for a physician to diagnose the disease quickly. Patient presenting with space occupying lesion in liver is confused with abscess, hepatoma or metastases. Here we are presenting a case report of isolated hepatic tuberculosis.Bangladesh J Medicine Jan 2015; 26 (1) : 43-45